2022
DOI: 10.1248/cpb.c21-00912
|View full text |Cite
|
Sign up to set email alerts
|

Bromine K-Edge X-Ray Absorption Near-Edge Structure Analysis on Hydrobromide-Salt Crystals and the Solid Dispersion of Active Pharmaceutical Ingredients

Abstract: Bromine K-edge X-ray absorption near-edge structure (XANES) spectroscopy analyses were used to evaluate the crystals of the active pharmaceutical ingredients, eletriptan hydrobromide, dextromethorphan hydrobromide and scopolamine hydrobromide salts and the solid dispersion of eletriptan hydrobromide. The crystals and the solid dispersion of the active pharmaceutical ingredient (API) salts could be discriminated based on the shape of the XANES spectra. The differences in the shape of XANES spectra was ascribabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…3a), considering the high reproducibility of this method. 9,11,16) Each spectrum had four peaks in this region. The peak heights of forms A and I were comparable, while the heights of the first and second peaks of form II were higher than those of forms A and I.…”
Section: Resultsmentioning
confidence: 99%
“…3a), considering the high reproducibility of this method. 9,11,16) Each spectrum had four peaks in this region. The peak heights of forms A and I were comparable, while the heights of the first and second peaks of form II were higher than those of forms A and I.…”
Section: Resultsmentioning
confidence: 99%
“…XANES spectroscopy is the method with a high element specificity and is suitable for detecting specifically the interatomic interactions at the X-ray absorbing atoms. The typical target elements of XANES spectroscopy in pharmaceutical research are chlorine, [9][10][11] bromine 12,13) and phosphorus, 14) although XANES may be applied, in principle, to all elements.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few studies on the method used for the evaluation of APIs. Two studies have used the XAFS method to investigate the chemical environment of Cl ion in clarithromycin hydrochloride hydrate salt form A and Br ion in eletriptan hydrobromide salt, respectively. , Other studies applied the method to mosapride salt and solvate crystals, indomethacin polymorphs and amorphous solid dispersions (ASDs), and disodium etidronate polymorphs and its amorphous form. All these studies showed that the shape of the XANES spectrum is changed by the weak noncovalent interatomic interactions such as hydrogen bond and halogen bond. Therefore, this method could be used to discriminate the crystal polymorphs of APIs.…”
Section: Introductionmentioning
confidence: 99%